Mid-life extra-haematopoetic manifestations of Diamond–Blackfan anaemia. (19th April 2017) - Muir, Christopher; Dodds, Anthony; Samaras, Katherine
Summary: Diamond–Blackfan anaemia (DBA) is a rare cause of bone marrow failure. The incidence of malignancy and endocrine complications are increased in DBA, relative to other inherited bone marrow failure syndromes. We describe an adult woman with DBA who developed osteoporosis and avascular necrosis (AVN) of both distal femora. Such endocrine complications are not uncommon in DBA, but under-appreciated, especially in adulthood. Further, rectal adenocarcinoma was diagnosed at age 32 years, requiring hemi-colectomy and adjuvant chemotherapy. Elevated cancer risk may warrant disease-specific screening guidelines. Genetic predictors of extra-haematopoetic complications in DBA are yet to be established. Learning points: Endocrine complications are common in DBA. Clinical vigilance is required in managing bone health of DBA patients treated with glucocorticoids. There is currently no reliable way to predict which patients will develop complications of therapy or premature malignancy related to DBA. Complaints of bone or joint pain should prompt screening with targeted magnetic resonance imaging. Osteoporosis screening should be performed routinely.